Comparative Biology and Reproductive Behaviour of A Laboratory- Adapted Redco Strain of Anopheles Gambiae Giles (Diptera; Culicidae) and Wild Populations of the Same Species. - Barfi, E (University of Ghana, 2015)
The sterile insect technique involves mass rearing of male insects for sterility purpose. This heavily relies on male fitness and genetic compatibility of laboratory-adapted male insects and the wild to ensure successful competition with their male counterpart in the wild. Uniform environment in the laboratory as compared to the wild conditions might lead to genetic drift which might lead to reduced sexual competitiveness, fitness, morphological changes or changes in the sexual behaviour of mosquitoes. This work investigated the sexual compatibility, morphometry and sexual behaviour of laboratory-adapted strain and wild strain of Anopheles gambiae under laboratory conditions. These measurements were done by observing swarm formation, genitalia rotation, percentage insemination, fecundity, fertility, wing length, wing width, thoracic width, body length, body size index and wing size index. Morphometric studies of laboratory-adapted and wild strain of Anopheles gambiae were carried out by observing the wing length, body length and thoracic length under Lecia 4D stereoscope in order to find out variations in the body size between the two strains. The results showed significant difference between thoracic width and wing length between the laboratory-adapted strain and wild strain. Indices such as body size index and wing length index also showed significant difference between the two strains; laboratory-adapted REDCO strain (BSI 4.45 ± 0.10, p = 0.010 ; WSI 1.92 ± 0.07, p = 0.026) and wild REDCO strain ( 4.08 ± 0.10, p = 0.010 ; WSI 1.73 ± 0.04, p = 0.026 ). Body length of laboratory-adapted male mosquitoes (4.24 ± 0.05, p = 0.462) was not significantly different from its thoracic width, wing length, and wing width. The wild strain on the other hand had significant difference between its body length (4.19 ± 0.04, p = 0.462), thoracic width (0.096 ± 0.02, p = 0.002 ) and wing length 2 (2.99 ± 0.03, p = 0.050 ). In the mating experiment, egg production in each of the crosses (W♂ x W♀; 594.00 ± 20.00, p = 0.00 ), (L♂ x L♀ ; 108.00 ± 119.00, p = 0.00) and (237.00 ± 40.00, p = 0.00) showed significance in egg production. The results suggest that sizes of the two strains differ and also laboratory-adapted strain produced the highest number of eggs.
Thesis (MPhil) - University of Ghana, 2015